Effect of thickness of the intumescent alkali aluminosilicate coating on temperature distribution in reinforced concrete. (December 2016) - Krivenko, Pavel V.; Guzii, Sergii G.; Bodnarova, Lenka; Valek, Jaroslav; Hela, Rudolf; Zach, Jiri
Abstract: The paper presents the results of investigations to determine the optimum thickness of intumescent aluminosilicate coating providing protection of concrete and reinforced concrete structures, in particular tunnels, in case of fire. It is shown that the developed intumescent aluminosilicate coating prevents heating of the surface structures of concrete and metal reinforcement of concrete to the limiting condition, i.e., to temperatures of 653 K and 773 K. The protective coating on the concrete surface, in thicknesses of 6 mm, can prevent concrete and reinforced concrete from brittle fracture and reinforcement from occurrence of plastic deformation for at least 2 h. The developed coatings were studied by heating the coated concrete surface using a spot fire (point source fire) for a period of 3 h, and temperatures beneath the coating and at a distance of 20 mm from the surface (embedded reinforcement) were measured. Measurements of pull-off adhesion of the coating were taken using an adhesion testing equipment before and after exposure of fire. Increasing the thickness of the protective coating reduces heating of the concrete in depth; the average temperature of the heating of the concrete at the depth of the metal reinforcement (20 mm) is 414.4 K, which is 1.9 times less than the limit of heating temperature of the metal fittings. The increase in thickness of the coating and time of fire exposure will result in even better heat insulating and fireproofing properties. Test results of the developed coating 6 mm in thickness suggested concluding that before exposure of fire type, its type of fracture – was А/В (concrete substrate/coating adhesion fracture) and its pull-off strength was 2.15 MPa. A mean value of adhesion (pull-off strength) of the developed coatings 12 and 18 mm in thickness was 1.55 MPa, type of fracture – В (cohesion fracture within the coating). After exposure of fire, not depending upon thickness of the coating, a mean value of adhesion (pull-off strength) was 0.85 MPa, type of fracture – В (cohesion fracture within the swollen porous coating). Highlights: A 6 mm- coating prevents concrete and reinforcement from destruction while heating. With increase in thickness protective properties of intumescent coatings increase. Fire exposure longer than 2 h does not affect protective properties.